2022
DOI: 10.1371/journal.pone.0262442
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Abbott SARS-CoV-2 IgG serological assay in South African 2 patients

Abstract: In late December 2019, pneumonia cases of unknown origin were reported in Wuhan, China. This virus was named SARS-CoV2 and the clinical syndrome was named coronavirus disease 19 (COVID-19). South Africa, despite strict and early lockdown has the highest infection rate in Africa. A key component of South Africa’s response to SARSCoV2 was the rapid scale-up of diagnostic testing. The Abbott SARS-CoV2 assay detects IgG antibodies against the Nucleocapsid (N) protein of the SARS-CoV2 virus. This study undertook to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 31 publications
(52 reference statements)
2
13
0
Order By: Relevance
“…Serology has played a key role in both retrospective and real-time modelling of the spread of SARS-CoV-2 infection and is useful in tracking asymptomatic transmission in ‘healthy’ individuals, such as healthcare workers and blood donors [ 1 , 4 , 11 , 15 ]. The results of the present study are consistent with previous findings on the performance of SARS-CoV-2 antibody diagnostic assays [ 16 ]. However, the majority of performance evaluation studies of SARS-CoV-2 serology assays have typically assessed sensitivity using samples from SARS-CoV-2 PCR positive patients at known time points after the onset of symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…Serology has played a key role in both retrospective and real-time modelling of the spread of SARS-CoV-2 infection and is useful in tracking asymptomatic transmission in ‘healthy’ individuals, such as healthcare workers and blood donors [ 1 , 4 , 11 , 15 ]. The results of the present study are consistent with previous findings on the performance of SARS-CoV-2 antibody diagnostic assays [ 16 ]. However, the majority of performance evaluation studies of SARS-CoV-2 serology assays have typically assessed sensitivity using samples from SARS-CoV-2 PCR positive patients at known time points after the onset of symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…After excluding studies which contained duplicate patient data, 77 studies comprising over 200,000,000 confirmed COVID-19 cases were included. 4 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the identification, screening, eligibility, and inclusion of the studies for the scoping review [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The quality assessment of the 17 articles resulted in four articles scoring 71% and the rest scoring 86% and above.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 provides an overview of the testing kits or methodology evaluated. Seven of the 17 studies included populations from Gauteng [ 17 , 19 , 21 , 22 , 24 , 29 , 30 ], four from the Western Cape [ 15 , 16 , 26 , 28 ], one from Limpopo [ 14 ], one from Eastern Cape [ 18 ], and one from the Free State [ 23 ]. Of the remaining three studies, two studies included samples from more than one province [ 20 , 27 ] and one study undertook testing on stored samples [ 25 ].…”
Section: Resultsmentioning
confidence: 99%